2021
DOI: 10.1007/978-3-030-75746-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Corruption Among Students in Latin America

Abstract: Anti-corruption reforms introduced in Latin America in the last decade require active citizenry. In particular, efforts to strengthen transparency laws assume citizens are able to identify, condemn, and denounce corrupt acts. Thus, tolerance of corruption among citizens is problematic for these institutions. Using data from IEA's International Civic and Citizenship Education Study (ICCS) 2016, this chapter analyzes which students are at higher risk of tolerating corruption and address how schools may promote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…They argued that researchers should employ various methodologies to assess their influence on attitudes, behaviors, and experiences to support the promotion of positive values and ethical behavior. Carrasco and Mediano [16] discovered that students with greater civic education are less tolerant of corruption, as it enables them to comprehend the repercussions and denounce corrupt behaviors. Denisova-Schmidt, Huber, and Leontyeva [17] found that higher-class students show a greater acceptance of corruption and informal behaviors, indicating that the higher education system can impact their views on corruption, which could result in adverse effects on society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argued that researchers should employ various methodologies to assess their influence on attitudes, behaviors, and experiences to support the promotion of positive values and ethical behavior. Carrasco and Mediano [16] discovered that students with greater civic education are less tolerant of corruption, as it enables them to comprehend the repercussions and denounce corrupt behaviors. Denisova-Schmidt, Huber, and Leontyeva [17] found that higher-class students show a greater acceptance of corruption and informal behaviors, indicating that the higher education system can impact their views on corruption, which could result in adverse effects on society.…”
Section: Literature Reviewmentioning
confidence: 99%